The Application of English Textbook in HSC Level: A Case Study in Bangladesh - Hani, Umme; Siddika, Mahmoda Khaton (American Journal of Humanities and Social Sciences, 2018)
National Curriculum and Textbook Broad, Bangladesh under the English Language Teaching Improvement Project has designed English textbook, English for Today, for classes 11 and 12 as a continuation of class 6 onwards following the principles of ‘practicing language activities’ ‘not knowing the rules of language’. This book targets four skills through the communicative approach and aims at using English for various purposes. But observation shows that there is a far discrepancy between text contents and testing system in board examination. Besides, our students are exam-oriented who use this book as a medium of academic excellence, not as a medium of language competence. For this, the application of this textbook is in question. This article aims at exploring the application of the HSC English textbook and investigates what the teachers and students focus on the text on and what they escape, and why they do so. The study has been done through both open-ended and close-ended questionnaires and interviews with teachers and students of some urban and rural colleges of Bangladesh. The study revealed that almost all teachers and students agree that the text is rich enough for acquiring all four language skills, but their learning and teaching activities are rather examination-oriented than acquiring language competency. The reshuffling of examination questionnaire in keeping with four language skills according to text can be a proper way to eliminate the gap between the textual contents, classroom and homework practices and testing system.